Prevalence of Cognitive Impairment/Dementia and Associated Risks Factors Among Community‐Dwelling Elderly People Aged 65 or Above in the Community Centers in Hong Kong: A Cross‐Sectional Study - Irelan Tam; Kailu Wang (Brain and Behavior)
ABSTRACT Backgrounds Dementia is a leading cause of morbidity and disability for elderly people worldwide, and prevalence rates of dementia are estimated to be 30% among people ≥80 years old. The burden of the disease could reach 11% of population aged over 60 in 2039. Objectives The study aims to report the prevalence rate of cognitive impairment/dementia among community‐dwelling elderly people aged ≥65 years old and identify the associated risk factors for dementia prevention. Methods This cross‐sectional study used non‐probability sampling technique. Participants 65 years old were interviewed using a structured questionnaire, and the Cantonese version of Mini‐Mental State Examination was used to screen for cognitive impairment/dementia. CMMSE score of ≤20 was the cut‐off points. Multivariate logistic regression was performed to examine risk factors associated with cognitive impairment/dementia. Results From 241 respondents, the study reported the overall prevalence of cognitive impairment/dementia was 18.9%, ranging between 13% and 33% in different age groups. Depression and those who belonged to lower socioeconomic status receiving Comprehensive Social Security Assistance were found to be significant risk factors for cognitive impairment/dementia. Conclusion The study showed higher overall prevalence of cognitive impairment/dementia in the community centers than previous studies and potentially high percentage of elderly with undetected dementia in the community. The finding highlighted the importance of increasing dementia literacy, strengthening health promotion for population‐wide screening with follow‐up diagnosis to enable early detection and subsequent interventions and treatments to improve the quality of dementia care for elderly in Hong Kong.